2022
DOI: 10.3390/s22113977
|View full text |Cite
|
Sign up to set email alerts
|

Non-Hermitian Sensing in Photonics and Electronics: A Review

Abstract: Recently, non-Hermitian Hamiltonians have gained a lot of interest, especially in optics and electronics. In particular, the existence of real eigenvalues of non-Hermitian systems has opened a wide set of possibilities, especially, but not only, for sensing applications, exploiting the physics of exceptional points. In particular, the square root dependence of the eigenvalue splitting on different design parameters, exhibited by 2 × 2 non-Hermitian Hamiltonian matrices at the exceptional point, paved the way t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 104 publications
(145 reference statements)
0
7
0
Order By: Relevance
“…Given the recent experimental realisation of hyperbolic lattices [8,9] using circuit quantum electrodynamics and the simulation of non-Hermitian phases using optical and electrical circuit elements [28][29][30], engineering non-Hermitian lattices in hyperbolic geometry is an experimentally viable endeavour. The abundance of EPs can have potential applications in designing non-Hermitian sensors operating on the scaling of eigenvalues near EPs [30][31][32]. We hope our work motivates further theoretical and experimental explorations of non-Hermitian hyperbolic matter.…”
Section: Discussionmentioning
confidence: 80%
“…Given the recent experimental realisation of hyperbolic lattices [8,9] using circuit quantum electrodynamics and the simulation of non-Hermitian phases using optical and electrical circuit elements [28][29][30], engineering non-Hermitian lattices in hyperbolic geometry is an experimentally viable endeavour. The abundance of EPs can have potential applications in designing non-Hermitian sensors operating on the scaling of eigenvalues near EPs [30][31][32]. We hope our work motivates further theoretical and experimental explorations of non-Hermitian hyperbolic matter.…”
Section: Discussionmentioning
confidence: 80%
“…Recently, NH topological phases have drawn considerable attention of the research community ranging from photonics to condensed matter physics [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45]. Dissipation in both classical and quantum mechanical systems is quite common, and this may lead to NH loss and gain.…”
Section: Introductionmentioning
confidence: 99%
“…10 More strikingly, an exceptional point (EP) was generated during the PT symmetry phase transition, whereby the eigenvalues and eigenstates degenerate simultaneously, thus resulting in some peculiar physical phenomena, such as unidirectional reflectionless, [11][12][13] asymmetric diffraction, 14 vortex generation, 15 polarization state transition, [16][17][18] chiral mode switching, 19 and sensing enhancement. [20][21][22] With thinner thickness, lower loss, and more flexible modulation than three-dimensional metamaterials, metasurfaces have become a favored platform for the study of PT symmetry by a wide range of researchers. Lawrence et al first observed PT symmetry breaking and EP in polarization space in a terahertz transmission metasurface composed of two resonant rings with mutually orthogonal openings.…”
Section: Introductionmentioning
confidence: 99%
“…10 More strikingly, an exceptional point (EP) was generated during the PT symmetry phase transition, whereby the eigenvalues and eigenstates degenerate simultaneously, thus resulting in some peculiar physical phenomena, such as unidirectional reflectionless, 11–13 asymmetric diffraction, 14 vortex generation, 15 polarization state transition, 16–18 chiral mode switching, 19 and sensing enhancement. 20–22…”
Section: Introductionmentioning
confidence: 99%